Biomass and nutrient content of sessile oak ( Quercus petraea (Matt.) Liebl.) and beech ( Fagus sylvatica L.) stem and branches in a mixed stand in southern Belgium - André, Frédéric; Jonard, Mathieu; Ponette, Quentin (The Science of the total environment, 2010)
Accurate estimates of the amounts of nutrients immobilised in the organs and tissues of different tree species are of prime importance to make appropriate tree species selection and determine the harvesting regime that will ensure forest sustainability. Sixteen sessile oaks ( Quercus petraea (Matt.) Liebl.) (64–129 years; stem diameters: 17–57 cm) and twelve beeches ( Fagus sylvatica L.) (43–86 years; stem diameters: 9–50 cm) were destructively sampled from a mixed stand located on an acid brown soil in southern Belgium. Statistical models were developed to investigate the differences in nutrient concentrations between tree species, between aboveground tree compartments of the same species, and between tissues of the same compartment. For stem tissues, vertical concentration profiles were described using a versatile equation. Allometric equations were used to predict biomass and nutrient content of tree compartments based on tree dimensions. Broadly speaking, nutrient concentrations tended to be somewhat higher for oak compared with beech, but the amplitude and the direction of inter-species differences varied greatly, depending on the nutrient and the tree compartment. For both species, living branch nutrient concentrations tended to decrease with increasing branch diameter, except for Ca (oak) and Mg (beech). Nutrient concentrations were consistently higher in bark than in wood; this difference between tissues was quite pronounced for Ca, particularly in the case of oak. The biomass and nutrient content equations were used to investigate the effects of tree species and harvesting regime on nutrient exports at harvesting. For equivalent harvesting scenarios, beech was found to induce higher Mg exports than oak, and inversely for Ca. Assuming stand clear cutting, complete tree harvesting would increase average nutrient exports from 65% (Ca) to 162% (P) compared with a stem-only harvesting scenario. These results provide valuable information in the current context of the more intensive utilization of forest products.